Edukasi Ibu Hamil Tentang Deteksi Kehamilan Resiko Tinggi Melalui Pemeriksaan Tripel Eliminasi - Sasanti, Dewi Ari; Novia Ningrum; Vannes Sukma Dewi; Putri Amelia; Nurlianti (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2024)
The triple elimination program aims to prevent transmission of HIV, syphilis and hepatitis B from mother to fetus. In 2021, 2,485,430 pregnant women were tested for HIV (50.8%), 799,586 pregnant women were tested for syphilis (16.4%), and 2,946,013 pregnant women were tested for hepatitis B (60 .3%).3 The gap between the number of HIV, syphilis and hepatitis B tests indicates that this triple elimination program is not yet a priority. This community service uses educational methods using booklet media. Activity participants are pregnant women of all trimesters and cadres. The pre-test and post-test results showed that the level of participants' understanding of Triple Elimination increased by 3.92% after education was provided through booklets. Community service activities showed positive responses from pregnant women and cadres in the discussion process regarding triple elimination problems for pregnant women. It is hoped that pregnant women can carry out triple elimination examinations, and better understand the importance of triple elimination, cadre mothers can play an active role in passing on information to prospective pregnant women and pregnant women who have not yet received information about Triple Elimination.   Abstrak Program triple elimination bertujuan untuk mencegah penularan HIV, sifilis, dan hepatitis B dari ibu kepada janin. Pada tahun 2021 ibu hamil yang melakukan pemeriksaan HIV sebanyak 2.485.430 orang (50,8%), jumlah ibu hamil dites sifilis yaitu sebanyak 799.586 orang (16,4%), dan ibu hamil dites hepatitis B sebanyak 2.946.013 orang (60,3%).3 Gaps antara jumlah pemeriksaan HIV, sifilis dan hepatitis B mengindikasikan bahwa program triple elimination ini belum semuanya menjadi prioritas. Pengabdian kepada masyarakat ini menggunakan metode edukasi dengan media booklet. Peserta kegiatan adalah ibu hamil semua trimester dan kader. Hasil pre test dan post test menunjukan tingkat pemahaman peserta tentang Triple Eliminasi meningkat sebanyak 3,92% setelah di lakukan edukasi melalui booklet. Kegiatan pengabdian kepada masyarakat menunjukkan tanggapan positif dari ibu hamil berserta kader dalam proses diskusi mengenai masalah-masalah triple eliminasi pada ibu hamil. Diharapkan ibu hamil dapat melaksanakan pemeriksaan triple eliminasi, dan lebih memahami pentingnya triple eliminasi, ibu kader dapat berperan aktif dalam meneruskan informasi kepada calon ibu hamil dan ibu hamil yang belum mendapatkam informasi tentang Triple eliminasi.